Rare and Endangered Flowering Plants of Bay Islands with Special Reference to Endemics and Extra Indian Taxa - Mandal, A. B.; Chattopadhyay, D.; Coomar, Tarun (Indian Forester, 2000)
The humid tropics of Andaman and Nicobar islands represent one of the richest repositories of diverse biota in South.East Asia. They fall in Indo.Malayan realm of the biosphere of earth and belong to Island biogeographic zone. A number of 2,200 angiosperm species belonging to 84 families lies scattered, approximately 10% of which (223) are said to be endemics, 110 are considered as rare threatened. Over 50 plant species have collected only once and never again (eg. Symplocos oxyphylla in 1884 and Habenaria andamanica in 1891) and are known only from type collections. A large number of species have already been extinct; a few are on their last legs. Anthropogenic reasons seems to be the driving force behind such tragedy impairing natural ecological processes crucial to our well being and affecting the resilience of the systems. As such, biotic pressures in solitary small Islands are intense and in such habitat threatened species do not find alternate habitat or refuges, ultimately wiped out in the 'death traps' of Islands. The present article summarises the status of rare and endangered flowering plants with special reference to distribution patterns of endemics and extra Indian species in Bay Islands.